1038. Rapid Start: A Changing Algorithm for the Management of HIV Infection. (31st December 2020) - Gudipati, Smitha; Jaziri, Miriam; Tancer, Stephanie; Vahia, Amit T; Brar, Indira
Abstract: Background: Initiating combination antiretroviral therapy (cART) as early as the day of HIV diagnosis is a strategy of increasing interest to control the HIV epidemic and optimize the health of people living with HIV. Pilot studies have shown that starting cART immediately after diagnosis has led to earlier linkage to care and HIV-1 RNA suppression. However, there is some evidence from observational studies that starting cART on the same day as HIV diagnosis may increase the risk of loss to follow-up. Consequently, there is a need for additional data for immediate cART initiation. Methods: A Retrospective cohort study was conducted from 2016 to 2018 to identify clinical characteristics and risk factors in patients that were diagnosed with HIV-1 with a 4th generation assay using electronic medical records. Rapid start was defined as offering cART prior to or on the first clinic visit. Categorical variables were analyzed using chi-sq test and continuous variables were analyzed using t-test. Data analysis was done using SAS 9.4. Results: In the study period, 188 patients were identified as HIV-1 positive and cART naïve: 152 males and 34 females. Risk factors included men who have sex with men (N = 86), heterosexual transmission (N = 88), intravenous drug use (N = 18) and multiple partners (N = 15). Of the 188 patients, 40 patients were rapidly started on cART on average within 6 days of diagnosis vs 42 days in the standard of care patients (P > 0.0001), with a shorter duration to clinic follow up over time (P = 0.3103). 50% patients that were rapid started on cART maintained an undetectable viral load vs 77% of the standard of care group (P = 0.3174). 90% of the rapid start patients were retained in care at 12 months vs 78% of the standard of care patients (P = 0.4950). 126 patients were started on single tablet regimens (P = 0.0001) with a trend favoring bictegravir, emtricitabine & tenofovir alafenamide (P = 0.0001). Conclusion: Our study adds to the growing data that rapid ART initiation within seven days of HIV diagnosis could reduce loss to follow‐up, improve virological suppression rates, and reduce mortality. The percentage of patients with undetectable HIV-1 viral load and retained in care was comparable to that in standard of care, indicating that starting cART immediately after diagnosis was well accepted by patients. Disclosures: Indira Brar, MD, Gilead (Speaker's Bureau)janssen (Speaker's Bureau)ViiV (Speaker's Bureau)